An Investigation of the Electrical Properties of Pressboard Impregnated with Mineral Oil-Based Nanofluids at Different Concentrations of Fe3O4 Magnetic Nanoparticles - Pichai Muangpratoom; Issaraporn Khonchaiyaphum; Wanwilai Vittayakorn (International Transactions on Electrical Energy Systems)
The purpose of this study was to investigate the electrical properties of pressboard impregnated with mineral oil-based nanomaterial. The nanomaterial focused on in this study was magnetite (Fe3O4) at ratios of 0.01%, 0.03%, and 0.05% by mineral oil volume. The electrical tests were performed on the AC breakdown strengths and positive-negative lightning impulse breakdown strengths on impregnated pressboard were carried out in compliance with IEC 60641 and IEC 60243, respectively. Scanning electron microscopy (SEM) and X-ray Diffraction (X-RD) were used to study the micro surface and show that Fe3O4 nanoparticles of nanoscale size were adhered to the pressboard surface and exist in an amorphous state. The results found that the AC breakdown strengths of pressboard impregnated with mineral oil-based Fe3O4 nanofluids at 0.03 wt% were increased the most. Moreover, the lightning impulse breakdown strengths of pressboard impregnated with mineral oil-based Fe3O4 nanofluids at 0.03 wt% were increased the most in both positive and negative polarities. The results, thus, showed promising directions for applications of Fe3O4 nanomaterials to improve the electrical properties of pressboard.